Thrombosis as a treatment complication in Hodgkin lymphoma patients: a comprehensive analysis of three prospective randomized German Hodgkin Study Group (GHSG) trials. (27th May 2019) - Borchmann, S; Müller, H; Hude, I; Fuchs, M; Borchmann, P; Engert, A
Abstract: Background: The prognosis of Hodgkin lymphoma (HL) is excellent rendering research into treatment complications highly important. An important complication of cancer and its treatment is thrombosis. Thrombotic events are regularly observed in HL patients but precise information on incidence and risk factors is lacking and the value of prophylactic anticoagulation unclear. Patients and methods: Thus, we comprehensively studied thrombotic events in 5773 patients from the German Hodgkin Study Group (GHSG) HD13–15 trials in early-favorable, intermediate and advanced HL. We estimated the incidence of and identified risk factors for thrombotic events. Additionally, we provide detailed data on the time course and characteristics of thrombotic events. Results: A total of 193 thrombotic events occurred for an incidence of 3.3%. Out of these, 175 (90.7%) were venous thromboses, 3 (1.5%) newly emerging post-thrombotic syndromes and 15 (7.8%) arterial thromboses. There were 11 (0.7%) events in early-favorable, 27 (1.3%) in early-unfavorable and 155 (7.3%) in advanced patients, the latter incidence being significantly higher ( P < 0.001). The most common locations were deep vein thrombosis of the arm (46.3%) and leg (24.6%). Most venous thrombotic events occurred during chemotherapy (78.9%). We observed 59 (30.6%) catheter-associated events and a descriptively increased risk of venous thrombotic events in patients with oral contraception use during treatment (6.8% versus 3.9%). In advanced HL, the incidence of venous thrombotic events was increased upon treatment with BEACOPP-14 (9.4%, P = 0.0079) compared with 5.1% with 6×BEACOPPesc and 5.7% with 8×BEACOPPesc. Among commonly applied risk factors, including the Khorana score, only age and smoking were prognostic. Conclusions: The incidence of thrombotic events in advanced stage HL is comparable to other high-risk cancer patients, especially if treated with dose-dense regimens. Additional risk factors are higher age and smoking. Selected HL patients could benefit from prophylactic anticoagulation, however, further interventional studies are needed before general recommendations can be made.